Some American voters are more equal : election law as an area of partisan strategy - Schwartz, Lauren; Thimm, Johannes (2017)
Zusammenfassung: Although Donald Trump ultimately won the presidency, he has claimed that Hillary Clinton only won the popular vote because millions of people had voted illegally. For years, accusations of electoral fraud have been used to increase the bureaucratic requirements for potential voters. Most of these tactics, which affect some demographic groups more than others, are legal. Republicans and Democrats alike have attempted to shape electoral districts to their advantage, resulting in politically more homogenous districts, more radical candidates, and ever-larger biases in the translation of votes into mandates. On October 3rd, the United States Supreme Court heard argu-ments on whether to curb the redistricting powers of the parties. The battles over election laws could have a long-term effect on future congressional majorities